Sensitivity calibration procedures in optical-CT scanning of BANG(®)3 polymer gel dosimeters - Xu, Y. (American Association of Physicists in Medicine, 2010)
The dose response of the BANG(®)3 polymer gel dosimeter (MGS Research Inc., Madison, CT) was studied using the OCTOPUS(™) laser CT scanner (MGS Research Inc., Madison, CT). Six 17 cm diameter and 12 cm high Barex cylinders, and 18 small glass vials were used to house the gel. The gel phantoms were irradiated with 6 and 10 MV photons, as well as 12 and 16 MeV electrons using a Varian Clinac 2100EX. Three calibration methods were used to obtain the dose response curves: (a) Optical density measurements on the 18 glass vials irradiated with graded doses from 0 to 4 Gy using 6 or 10 MV large field irradiations; (b) optical-CT scanning of Barex cylinders irradiated with graded doses (0.5, 1, 1.5, and 2 Gy) from four adjacent 4×4 cm(2) photon fields or 6×6 cm(2) electron fields; and (c) percent depth dose (PDD) comparison of optical-CT scans with ion chamber measurements for 6×6 cm(2), 12 and 16 MeV electron fields. The dose response of the BANG(®)3 gel was found to be linear and energy independent within the uncertainties of the experimental methods (about 3%). The slopes of the linearly fitted dose response curves (dose sensitivities) from the four field irradiations (0.0752±3%, 0.0756±3%, 0.0767±3%, and 0.0759±3% cm(−1) Gy(−1)) and the PDD matching methods (0.0768±3% and 0.0761±3% cm(−1) Gy(−1)) agree within 2.2%, indicating a good reproducibility of the gel dose response within phantoms of the same geometry. The dose sensitivities from the glass vial approach are different from those of the cylindrical Barex phantoms by more than 30%, owing probably to the difference in temperature inside the two types of phantoms during gel formation and irradiation, and possible oxygen contamination of the glass vial walls. The dose response curve obtained from the PDD matching approach with 16 MeV electron field was used to calibrate the gel phantom irradiated with the 12 MeV, 6×6 cm(2) electron field. Three-dimensional dose distributions from the gel measurement and the Eclipse planning system (Varian Corporation, Palo Alto, CA) were compared and evaluated using 3% dose difference and 2 mm distance-to-agreement criteria.